MBCL-29. PHASE I/II STUDY OF SEQUENTIAL HIGH-DOSE CHEMOTHERAPY WITH STEM CELL SUPPORT IN CHILDREN YOUNGER THAN 5 YEARS OF AGE WITH HIGH-RISK MEDULLOBLASTOMA. (4th December 2020) - Dufour, Christelle; Masliah-Planchon, Julien; Delisle, Marie-Bernadette; Geoffray, Anne; Abbas, Rachid; Bourdeaut, Franck; Bertozzi, Anne-Isabelle; Faure-Conter, Cecile; Chappe, Celine; De Carli, Emilie; Entz-Werle, Natacha; Fouyssac, Fanny; et al.
Abstract: PURPOSE: To assess the 3-year EFS rate of children younger than 5 years of age with high-risk medulloblastoma (MB) treated according to the prospective multicenter trial HR MB-5. PATIENTS AND METHODS: After surgery, all children received 2 cycles of Etoposide- Carboplatine. If partial (PR) or complete response (CR) was achieved after induction chemotherapy, children received 2 courses of thiotepa (600mg/m²) with stem cell rescue. For patients in CR after high-dose chemotherapy, they received one course of Cyclophosphamide – Busilvex with stem cell rescue (Phase I part). The others patients (not in PR after induction or in CR after thiotepa) were treated with 2 cycles of Temozolomide-Irinotecan followed by age-adapted craniospinal irradiation and maintenance treatment. RESULTS: 28 children (2 to 4 years; median: 3.0 years) were enrolled. Group 3 MB were most common (57%). The response rate to Etoposide-Carboplatine was 60.7%. Among 20 patients treated with Thiotepa, 13 children were in CR and received Cyclophosphamide – Busilvex without radiotherapy. Out of them, 9 patients (45%) are alive in CR without craniospinal irradiation (median follow-up 5 years). Among 15 patients treated with radiotherapy, 8 patients are alive (median follow-up 3.8 years). The study was prematurely stopped for an excess of events. The median follow-up was 4 years (range 1.5 - 6.1). The 3-year EFS and OS were 42.3% [25.9 - 60.6] and 71.3% [52.7 - 84.7], respectively. CONCLUSIONS: This risk-adapted strategy did not improve EFS in young children with high-risk MB. However, the study shows that good responders to chemotherapy can be cured without recourse to irradiation.